Proyeksi Skala Usaha Anggrek Dendrobium dengan Penerapan Variasi Dosis Pupuk untuk Memacu Pertumbuhan Fase Remaja ke Fase Pembungaan - Jian Tikasari; Maria Ulfah; Ipah Budi Minarti (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This research aims to determine the projected scale of the Dendrobium orchid business by applying variations in fertilizer doses to stimulate growth from the juvenile phase to the flowering phase. The type of research used in this research is experimental research. This research used a RAL (Completely Randomized Design) experimental design with five replications. The results of the research showed that orchid plants that were given a fertilizer concentration of 1 g/L had a greater number of panicles and panicle length growth was faster compared to other fertilizer concentrations. Conclusion: Using a fertilizer concentration of 1 gram/L provides an advantage in the basic price of one plant with the selling price being able to meet the basic needs of growing orchid plants. Keywords: Dendrobium Orchid, Fertilizer Concentration, Business Scale